Cellular preservation of musculoskeletal specializations in the Cretaceous bird Confuciusornis - Baoyu Jiang (Nature Portfolio, 2017)
Birds have a more crouched posture compared to their theropod dinosaur ancestors. Here, Jiang and colleagues describe a lower hindlimb of the Early Cretaceous birdConfuciusorniswith soft tissues apparently preserved even as molecules, indicating a somewhat more modern posture in ancient birds.